Assessment for Melting Temperature Measurement of Nucleic Acid by HRM. (19th October 2016) - Wang, Jing; Pan, Xiaoming; Liang, Xingguo
Abstract : High resolution melting (HRM), with a high sensitivity to distinguish the nucleic acid species with small variations, has been widely applied in the mutation scanning, methylation analysis, and genotyping. For the aim of extending HRM for the evaluation of thermal stability of nucleic acid secondary structures on sequence dependence, we investigated effects of the dye of EvaGreen, metal ions, and impurities (such as dNTPs) on melting temperature (T m ) measurement by HRM. The accuracy of HRM was assessed as compared with UV melting method, and little difference between the two methods was found when the DNAT m was higher than 40°C. Both insufficiency and excessiveness of EvaGreen were found to give rise to a little bit higherT m, showing that the proportion of dye should be considered for preciseT m measurement of nucleic acids. Finally, HRM method was also successfully used to measureT m s of DNA triplex, hairpin, and RNA duplex. In conclusion, HRM can be applied in the evaluation of thermal stability of nucleic acid (DNA or RNA) or secondary structural elements (even when dNTPs are present).